what product is being shown
5+ (6+3) = (5+6)+3
9 answers
The product being shown is the equality of two equations, not a physical product. The equation is demonstrating the associative property of addition, which states that changing the grouping of numbers being added does not change the sum. In this case, the equation is showing that adding 6 and 3 first (inside the parentheses) and then adding 5, is equal to adding 5 and 6 first and then adding 3.
What property is being shown?
〖5x〗^3∙1=5x^3
〖5x〗^3∙1=5x^3
The property being shown is the identity property of multiplication. This property states that when any number is multiplied by 1, the product is equal to the original number. In this case, multiplying 5x^3 by 1 results in 5x^3, indicating that the value of the expression remains the same.
Evaluate:
-5∙-√25=
-5∙-√25=
To evaluate the expression -5∙-√25, we first need to simplify the square root of 25, which is 5. Thus, we have -5∙-5.
When we multiply two negative numbers together, the result is positive. Therefore, -5∙-5 equals 25.
Therefore, -5∙-√25 simplifies to 25.
When we multiply two negative numbers together, the result is positive. Therefore, -5∙-5 equals 25.
Therefore, -5∙-√25 simplifies to 25.
Simplify the expression:
6(-5n+7)=
6(-5n+7)=
To simplify the expression 6(-5n + 7), we can distribute the 6 to each term inside the parentheses.
6 * -5n = -30n
6 * 7 = 42
Therefore, the simplified expression is -30n + 42.
6 * -5n = -30n
6 * 7 = 42
Therefore, the simplified expression is -30n + 42.
Simplify the expression:
-3(4a-5b)=
-3(4a-5b)=
To simplify the expression -3(4a - 5b), we can distribute the -3 to each term inside the parentheses.
-3 * 4a = -12a
-3 * -5b = 15b
Therefore, the simplified expression is -12a + 15b.
-3 * 4a = -12a
-3 * -5b = 15b
Therefore, the simplified expression is -12a + 15b.